Exploration and analysis of the value of tumor-marker joint detection in the pathological type of lung cancer - Gao, Shuhui; Zhang, Guibin; Lian, Yufei; Yan, Li; Gao, Haixiang (Cellular and Molecular Biology, 2020)
Lung cancer is a disease characterized by the uncontrolled growth of cells in lung tissue. If left untreated, cell growth can spread beyond the lungs to a process called metastasis and reach surrounding tissues or other organs. This experiment was set up to discuss and analyze the research value of joint detection of tumor markers including carcino-embryonic antigen (CEA), cytokeratin 19 fragments (CYFRA21-1) and neuron-specific enolase (NSE) in the diagnosis and pathological type of lung cancer. From November 2016 to February 2018, 378 cases of patients with lung cancer treated in our hospital and 200 cases of people with healthy physical examinations were collected. The electrochemical immunoluminescence method was adopted to detect the CEA, CYFRA21-1 and NSE. The detected positive rate and the concentration of CEA, CYFRA21-1 and NSE of lung cancer group were higher than that of the healthy physical examination group. The differences were of statistical significance (P<0.05); the detected positive rate of CEA and CYFRA21-1 and the concentration of CEA, CYFRA21-1 and NSE of squamous carcinoma group were higher than that of the adenocarcinoma group. The differences were of statistical significance (P<0.05). The CEA, CYFRA21-1 and NSE are related to the pathological type of lung cancer and can be regarded as related indicators to diagnose lung cancer.